2012
DOI: 10.1101/gad.193136.112
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular matrix proteoglycan perlecan facilitates transmembrane semaphorin-mediated repulsive guidance

Abstract: The Drosophila transmembrane semaphorin-1a (Sema-1a) is a repulsive guidance cue that uses the Plexin A (PlexA) receptor during neural development. Sema-1a is required in axons to facilitate motor axon defasciculation at guidance choice points. We found that mutations in the trol gene strongly suppress Sema-1a-mediated repulsive axon guidance. trol encodes the phylogenetically conserved secreted heparan sulfate proteoglycan (HSPG) perlecan, a component of the extracellular matrix. Motor axon guidance defects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 59 publications
2
38
0
1
Order By: Relevance
“…Sema-1a is enriched in Drosophila embryonic neurons and mediates axonal repulsion, ensuring proper axon pathfinding (Winberg et al, 1998b;Yu et al, 1998;Ayoob et al, 2004;Cho et al, 2012;Jeong et al, 2012). During neural development, motor axons exit the CNS in two large bundles that include multiple motor axons which then segregate into smaller motor nerves: the intersegmental nerves (ISNs: ISNb and ISNd) and the segmental nerves (SNs: SNa and SNc) (Landgraf et al, 1997).…”
Section: Gyc76c Suppresses Sema 1a-mediated Motor Axon Repulsionmentioning
confidence: 99%
“…Sema-1a is enriched in Drosophila embryonic neurons and mediates axonal repulsion, ensuring proper axon pathfinding (Winberg et al, 1998b;Yu et al, 1998;Ayoob et al, 2004;Cho et al, 2012;Jeong et al, 2012). During neural development, motor axons exit the CNS in two large bundles that include multiple motor axons which then segregate into smaller motor nerves: the intersegmental nerves (ISNs: ISNb and ISNd) and the segmental nerves (SNs: SNa and SNc) (Landgraf et al, 1997).…”
Section: Gyc76c Suppresses Sema 1a-mediated Motor Axon Repulsionmentioning
confidence: 99%
“…In mammals, activation of integrins signals through focal-adhesion kinase (FAK) family proteins to promote outgrowth of neurites (Ivankovic-Dikic et al, 2000), and semaphorin treatment has been shown to exert changes on Fak phosphorylation (Cho et al, 2012). Therefore, we tested if Fak is also required for dendrite-ECM adhesion in class IV da neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies show that crosstalk between semaphorin and integrin signaling leads to inhibition of integrin-mediated adhesion in both invertebrates and vertebrates (Tamagnone and Comoglio, 2004; Kruger et al, 2005; Cho et al, 2012). For example, semaphorin-mediated signaling decreases integrin-mediated attachment during vascular morphogenesis (Serini et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This forward signaling cascade is modulated by perlecan, an extracellular matrix component, which enhances semaphorin-induced downregulation of integrin adhesive function and FAK dephosphorylation, leading to motor axon defasciculation. 15 Notably, Sema1a can also mediate motor axon defasciculation through reverse signaling mechanisms, whereby its cytoplasmic domain can interact with two major antagonistic regulators of the GTPase Pebble and the inhibitor RhoGAP p190. The first activates Rho1 and promotes axon-axon repulsion and defasciculation, while p190-RhoGAP antagonizes this mechanism allowing axonal attraction; 16,17 the extracellular Sema1a-binding molecule triggering this cascade is still unclear.…”
Section: Bidirectional Signaling Of Transmembrane Semaphorinsmentioning
confidence: 99%